2022
DOI: 10.1161/hypertensionaha.122.18970
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Renin-Angiotensin-Aldosterone System Inhibitors on the Rupture Risk Among Hypertensive Patients With Intracranial Aneurysms

Abstract: Background: Mounting experimental evidence supports the concept that the RAAS (renin-angiotensin-aldosterone system) is involved in the pathogenesis of intracranial aneurysm rupture. However, whether RAAS inhibitors could reduce the rupture risk of intracranial aneurysms remains unclear. Methods: We performed a chart review of a multicenter, prospectively maintained database of 3044 hypertensive patients with intracranial aneurysms from 20 medical cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
5
2
Order By: Relevance
“…Despite numerous observational studies showing that ARB and ACEI may be protective for aneurysm rupture, 4 our study failed to confirm these associations. However, our results cannot completely rule out their effect on IA/SAH because the limited number of SNPs in this study may not provide sufficient statistical power.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Despite numerous observational studies showing that ARB and ACEI may be protective for aneurysm rupture, 4 our study failed to confirm these associations. However, our results cannot completely rule out their effect on IA/SAH because the limited number of SNPs in this study may not provide sufficient statistical power.…”
Section: Discussioncontrasting
confidence: 95%
“…However, the literature is inconclusive in this regard. For example, while some studies suggest that ARBs and ACEI are effective in preventing aneurysm rupture, 4 others found no such effect. 5 One cross-sectional study even found CCBs were independently associated with the presence of IAs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous observational studies showing that ARB and ACEI may be protective against aneurysm rupture, 29 our study failed to confirm these associations. However, our results cannot completely rule out their effect on IA/SAH because the limited number of SNPs in this study may not provide sufficient statistical power.…”
Section: Discussioncontrasting
confidence: 93%
“…Our results also suggest that a history of hypertension and higher AR increase the rupture risk of PcomA aneurysms. Previous studies suggested that hypertension may be involved in aneurysm rupture through the renin–angiotensin–aldosterone system, and the latest multicenter study demonstrated that the risk of aneurysm rupture due to hypertension could be significantly reduced using renin–angiotensin–aldosterone system inhibitors ( 44 ). A large cohort study also showed recently that higher AR was an independent predictor of aneurysm rupture ( 45 ).…”
Section: Discussionmentioning
confidence: 99%